2017
DOI: 10.3171/2016.11.spine16488
|View full text |Cite
|
Sign up to set email alerts
|

Superficial siderosis of the central nervous system associated with intraspinal hemorrhage from ventral thoracic epidural veins and a ventral spinal CSF leak: case report

Abstract: In most patients with superficial siderosis of the CNS, the exact source of bleeding remains unknown because of a lack of objective surgical data. The authors herein describe the case of a 58-year-old man with superficial siderosis of the CNS. The patient also had spinal CSF leakage due to a spinal dural defect. Repair surgery for the dural defect was performed using posterior laminoplasty with a transdural approach without spinal fixation. During repair surgery, the bleeding source was found to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…However, the exact bleeding source remains unknown because of a lack of objective data, even in patients who have undergone neurosurgery. 5,10 This case shows a possible mechanism of chronic bleeding from an osteophyte into the subarachnoid space. In the currently available literature, a perforating artery on an osteophyte bleeding into the subarachnoid space has not been described.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the exact bleeding source remains unknown because of a lack of objective data, even in patients who have undergone neurosurgery. 5,10 This case shows a possible mechanism of chronic bleeding from an osteophyte into the subarachnoid space. In the currently available literature, a perforating artery on an osteophyte bleeding into the subarachnoid space has not been described.…”
Section: Discussionmentioning
confidence: 90%
“…Arresting the bleeding into the subarachnoid space seems to be accompanied by clinical stability or improvement that may sometimes be subjective. 3,8,10 Despite extensive investigations (brain and spine MRI, CT myelography, MR angiography, cerebrospinal angiography), the cause of bleeding is often not apparent. The identified sources of recurrent bleeding in SSCNS have typically included neoplasms, vascular malformations, brachial plexus or nerve root injury or avulsion, and previous head and spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first report by Kumar et al, SS with associated VLISFC has been reported by several institutions [1,[13][14][15]. In 2012, Kumar et al also reported cases of VLISFC due to CSF leakage from dural defects in diseases such as SS, craniospinal hypovolemia, and spinal cord herniation [1,16,17].…”
mentioning
confidence: 99%